Rancang Bangun Sistem Monitoring Kesehatan Balita Berbasis Aplikasi Mobile pada Posyandu Sripemandang - Aulia, Rosaura; Fujiyanti, Linda; Swengky, Better (Jurnal Teknologi, 2025)
The rapid advancement of information technology has significantly impacted various sectors, including healthcare. One of the community health services that requires digital innovation is Posyandu, which plays a vital role in monitoring the growth and development of toddlers. The manual data recording process often causes problems such as data loss and delayed information delivery. This research aims to design and develop a mobile-based information system for Posyandu to simplify the process of recording, managing, and monitoring toddler health data in an integrated manner. The development method used is the Prototyping Method, which allows iterative system development based on user requirements. Data were collected through interviews and direct observations at Posyandu Sripemandang to identify user needs, followed by system design using UML diagrams (Use Case, Activity, Sequence, and Class Diagrams). The implemented system includes main features such as child registration, digital medical records, growth charts, Posyandu schedules, and health information updates. System testing was conducted using User Acceptance Testing (UAT) and Blackbox Testing methods to evaluate functionality and user satisfaction. The test results show an index value of 85.48%, indicating that the system is highly feasible and that all features function as intended. Overall, the system effectively improves efficiency, accuracy, and accessibility of toddler health data management for midwives, Posyandu cadres, and parents in Posyandu Sripemandang.